THE EFFFECT OF GRAIN SIZE AND APPLIED STRESS IN HYDROGEN EMBRITTLEMENT PHENOMENA ON LOW CARBON STEEL - RACHMAN (NIM : 13707024); Dosen Pembimbing : Dr.Ir. Bambang Widyanto, ANDIKA
Hydrogen embrittlement is a phenomenon that could cause failure of industrial components, such as oil and gas pipelines which are made of low carbon steel. The existence of hydrogen in low carbon steel can degrade the mechanical properties of low carbon steel, for example decreasing ductility, toughness, and tensile strength. In this experiment, hydrogen charging, a electrochemistry process, was used as a method to let hydrogen enter the material. Specimen was put as the cathode in this process. Notched specimen was given an applied stress during the hydrogen charging to concentrate the hydrogen concentration on area of the highest stress concentration. Variation of grain size of the specimens was made by heating each specimen in 900oC with different heating time. The tensile test was conducted to compare the mechanical properties of charged and uncharged specimens. The result of the experiment indicate some changing in mechanical properties of material, such as increasing tensile strength, decreasing elongation, and decreasing toughness of material. The bigger specimen grain size, the smaller the effect of hydrogen on specimen. Specimen with grain size of 11.2 μm has its tensile strength increased by 9.76%, elongation increased by 52,2%, and toughness increased by 46.98%. . Specimen with grain size of 26.7 μm has its tensile strength increased by 3.58%, elongation increased by 25%, and toughness increased by 21.77%.